circSLC6A6 Sponges miR-497-5p to Promote Endometrial Cancer Progression via the PI4KB/Hedgehog Axis - Juan Hu; Xing Peng; Weina Du; Yichuan Huang; Chun Zhang; Xian Zhang (Journal of Immunology Research)
Background. As a new kind of noncoding RNAs, circular RNAs (circRNAs) have been substantiated to be involved in multiple biological processes. Accumulating studies indicate that circular RNAs (circRNAs) regulate the development of cancers by acting as miRNA sponges. However, the role of circRNAs in endometrial cancer (EC) is rarely reported. This study was aimed at investigating the functional roles of circSLC6A6 in EC. Methods. The qRT-PCR assay was performed to detect the circSLC6A6 expression in EC tissues and cell lines. The luciferase reporter assay was performed to explore the connection between circSLC6A6 and miR-497-5p as well as the connection between miR-497-5p and PI4KB. The colony formation assay, EdU assay, wound healing assay, and transwell assay were performed to examine the proliferation, migration, and invasion of EC cells. The in vivo assay was performed to reveal the function of circSLC6A6 in tumorigenesis. Results. We found that circSLC6A6 was highly expressed in both EC tissues and cells. And circSLC6A6 promoted the proliferation, migration, and invasion of EC cells in vitro. In vivo, circSLC6A6 promoted tumor growth. Besides, a mechanistic study demonstrated that circSLC6A6 could regulate tumor-associated signaling PI4KB/hedgehog pathway by sponging miR-497-5p. Conclusion. This study illustrates that circSLC6A6 plays a role in promoting EC progression via the miR-497-5p-mediated PI4KB/hedgehog pathway. Our study may provide a potential novel biomarker for EC diagnosis or treatment.